Type 2 diabetes is associated with pulmonary cavitation in men with HIV-TB coinfection - Mao, Yongkang; Zhao, Bennan; Lan, Lijuan; Gao, Fengjiao; Ren, Xiaoxia; Du, Jingchang; Zhu, Yanfeng; Liu, Dafeng (Frontiers in Endocrinology, 2026)
ObjectivesTo explore the association between type 2 diabetes mellitus (T2D) and pulmonary cavitation in male with HIV–tuberculosis (TB) coinfection, as well as to quantify the relationships between glycemic indicators [HbA1c and fasting plasma glucose (FPG)] and cavity size. The robustness of these correlations was further validated in a non-HIV TB sample.MethodsThis comparative cross-sectional study based on exposure status included 132 men with HIV–TB and T2D (exposed group) and 131 age-matched men with HIV–TB without T2D (non-exposed group). Multivariable regression models, subgroup analyses, and interaction tests were used to evaluaterelationships and effect modification. A validation cohort of 100 non-HIV TB patients was analyzed using the same analytical framework.ResultsIn men coinfected with HIV and TB, T2D was linked to a higher incidence of pulmonary cavitation (adjusted OR = 3.892, 95% CI = 1.895-7.992, P<0.001). HbA1c (B = 1.039, P = 0.049) and FPG (B = 0.869, P<0.001) are positively correlated with cavity size. A notable interaction was detected between T2D and sputum positivity (P<0.001), indicating the greatest incidence of cavitation in sputum-positive T2D patients (OR = 10.492, 95% CI = 3.266–33.711). Consistent results were found in the non-HIV TB group (T2D-related cavitation OR = 4.110, P = 0.014), demonstrating that the effect of T2D is not modified by HIV status.ConclusionT2D is a significant risk factor for pulmonary cavitation in males with HIV–TB coinfection, and poor glycemic management is linked with increased cavity size. Sputum-positive patients with T2D represent an exceptionally high-risk subgroup. Incorporating glycemic evaluation and optimal metabolic management into TB care may assist to lower cavitation risk in this population.